Engineering Education and Technological / Professional Learning - Viegas, Clara (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The focus of this Special Issue is aimed at enhancing the discussion of Engineering Education, particularly related to technological and professional learning. In the 21st century, students face a challenging demand: they are expected to have the best scientific expertise, but also highly developed social skills and qualities like teamwork, creativity, communication, or leadership. Even though students and teachers are becoming more aware of this necessity, there is still a gap between academic life and the professional world. In this Special Edition Book, the reader can find works tackling interesting topics such as educational resources addressing students' development of competencies, the importance of final year projects linked to professional environments, and multicultural or interdisciplinary challenges.